Randomised, multicentre, placebo-controlled trial of fenofibrate for treatment of diabetic macular oedema with economic evaluation (FORTE study): study protocol for a randomised control trial - Gerald Liew; Paul Mitchell; Bamini Gopinath; Helen Nguyen; Richard Kha (BMJ Open)
Introduction Diabetic macular oedema (DMO), a serious ocular complication of diabetic retinopathy (DR), is a leading cause of vision impairment worldwide. If left untreated or inadequately treated, DMO can lead to irreversible vision loss and blindness. Intravitreal injections using antivascular endothelial growth factor (anti-VEGF) and laser are the current standard of treatment for DMO. These treatments are costly and invasive and must be repeated over several years with a high service load. Fenofibrate has been shown to reduce the progression of DR. However, there is a lack of high-quality data on the effects of fenofibrate on established DMO. This study aims to evaluate the effectiveness of oral fenofibrate for the treatment of DMO.Methods and analysis This randomised double-blind, placebo-controlled trial recruited 204 patients with DMO across three different clinics in Sydney. Participants will be randomly allocated in a 1:1 ratio to intervention and control groups. The intervention group will receive oral fenofibrate (145 mg) taken once daily for 24 months, while the control group will receive placebo tablets taken once daily for 24 months. Standard care with anti-VEGF injections, focal lasers or observation will also be provided to all participants regardless of their group allocation. The primary outcome is the reduction in DMO measured using central macular subfield thickness (CSMT) on optical coherence tomography imaging at 24 months. Secondary outcomes at 24 months include the proportion of eyes with CSMT <250 µm, number of anti-VEGF injections, number of laser sessions needed, best-corrected visual acuity letter score gains, rates of adverse events, progression in DR lesions and changes in quality of life measures. Comparison between groups will be evaluated using analysis of variance. Multiple regression analyses adjusting for age, glycated haemoglobin, number of injections and other covariates will also be performed.Ethics and dissemination Ethics approval has been granted by the University of Sydney Human Ethics Committee (HREC-2019/892), and the trial has been registered with the Australia New Zealand Clinical Trials Registry (ACTRN12618000592246). The study adheres to the principles of the Helsinki Declaration and the National Health and Medical Research Council National Statement on Ethical Conduct in Human Research. Trial results will be disseminated to the public in de-identified form through publications in peer-reviewed journals.Trial registry name Australian New Zealand Clinical Trials Registry.Trial registration number ACTRN12618000592246.